PENGGUNAAN MEDIA RODA BERPUTAR UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SDN 31 CAKRANEGARA - Syukron Zul Ramdan (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2024)
This study aims to determine the effectiveness of the use of rotating wheel media in encouraging the learning interest of grade V students of SDN 31 Cakranegara. Problems in the learning process can occur, one of which is that the media used is not appropriate. This study uses a qualitative approach with a descriptive method and the collection of data use techniques using field research and library research. The results of the experiment of spinning wheel media in grade V of SDN 31 Cakranegara showed that students showed interest in learning when using spinning wheel media, this was shown by the enthusiastic attitude of students during the learning process.